[Kennedy Library dedication ceremony] - P. K. Phillips::::::photographer::: (1981)
View of the audience present for the dedication of the library under the name of Robert E. Kennedy. This took place at the main entrance to the library. A person is standing behind the podium, speaking to the crowd. Some of the people present are: President Warren Baker, Dale Andrews, President Robert E. Kennedy, and the director of the library, Walsh.